Community-level prevalence of epilepsy and of neurocysticercosis among people with epilepsy in the Balaka district of Malawi: A cross-sectional study - Luise Keller; Dominik Stelzle; Veronika Schmidt; Hélène Carabin; Ann-Kristin Reinhold; Claudius Keller; Tamara M. Welte; Vivien Richter; Action Amos; Lindsay Boeckman; Wendy Harrison; Andrea S. Winkler (Public Library of Science (PLoS), 2022)
Background Epilepsy and neurocysticercosis (NCC) prevalence estimates in sub-Saharan Africa are still scarce but show important variation due to the population studied and different screening and diagnosis strategies used. The aims of this study were to estimate the prevalence of epileptic seizures and epilepsy in the sampled population, and the proportion of NCC among people with epilepsy (PWE) in a large cross-sectional study in a rural district of southern Malawi. Methods We conducted a community-based door-to-door screening study for epileptic seizures in Balaka, Malawi between October and December 2012. Past epileptic seizures were reported through a 15-item questionnaire answered by at least one person per household generating five major criteria. People who screened positive were further examined by a neurologist to establish diagnosis. Patients diagnosed with epilepsy were examined and offered Taenia solium cyst antigen and antibody serological tests, and a CT scan for the diagnosis of NCC. Results In total, screening information on 69,595 individuals was obtained for lifetime occurrence of epileptic seizures. 3,100 (4.5%) participants screened positive, of whom 1,913 (62%) could be followed-up and underwent further assessment. Lifetime prevalence was 3.0% (95% Bayesian credible interval [CI] 2.8 to 3.1%) and 1.2% (95%BCI 0.9 to 1.6%) for epileptic seizures and epilepsy, respectively. NCC prevalence among PWE was estimated to be 4.4% (95%BCI 0.8 to 8.5%). A diagnosis of epilepsy was ultimately reached for 455 participants. Conclusion The results of this large community-based study contribute to the evaluation and understanding of the burden of epilepsy in the population and of NCC among PWE in sub-Saharan Africa. Author summary Epilepsy is more common in low-income and middle-income countries than in high-income countries. One of the reasons for this is that risk factors for acquired epilepsy such as Taenia solium cysticercosis are more common in these countries. In this study we conducted a screening for epileptic seizures among nearly 70,000 people of rural Balaka district of Malawi. We found that around 3 percent of people have ever experienced an epileptic seizure and that 1 percent of people suffer from epilepsy. The screening questionnaire that we used was quite accuracte, and the more criteria for screening positive were fulfilled, the more likely it was that the person has ever experienced an epileptic seizure. Among the patients with epilepsy, around 5% also had neurocysticercosis typical lesions in their brain.